A New EOR Technology: Gas Alternating Gas Injection - Samba, Mohammed Alsharif; Aldokali, Ibrahim; Elsharaf, Mahmoud Omran (Journal of Earth Energy Engineering, 2019)
A new method of enhanced oil recovery has been developed and applied to a simulation using some of data from the fifth SPE paper " template from CMG ". The simulator was used in this paper is GEM in the Computer Modelling Group (CMG) advanced equation-of-state (EOS) compositional simulator. The new method is called Gas alternating gas injection(GAG). The Gas Alternating Gas process is a cyclic method of injecting alternating cycles of gas followed by gas and repeating. Sensitivity analysis showed this method can give a much better recovery factor for GAG compared with single continues gas injection. GAG benefits that will give low water cut and high oil recovery due to gas segregation between two gases and that will prevent heavier gas to go the top layers. This work indicate that the GAG injection is an economic method compared with continues injection. Especially when we use GAG (Air + CO2).